Corporate Social Responsibility: An International Study The Case of CGD (Portugal), Vale (Brazil), TechnoLogica (Bulgaria) and IndianOil (India) - Filipe, José António (2013)
There are many studies in the area of Corporate Social Responsibility but the presentation of several cases in one study reveals some particular aspects to be considered and to be had in account when CSR is studied. There are developments on this matter showing that progressively an increasing number of companies are concerned about their performance on this subject and about reaching their objectives involving CSR. Corporate Social Responsibility shall have self-regulating mechanisms through which responsibilities shall be monitored. Companies shall ensure that law is guaranteed as far as ethical standards and international norms shall be assured as well. According to the 2001 European Commission Green Paper, Social Responsibility conceptualization is associated with the idea of companies deciding, in a voluntary base, to contribute for a fair society and a cleaner environment. Corporate social responsibility deals with the organizations’ actions intending to get a positive impact on several areas, such as environment, consumers, employees or communities, for instance. It demands a set of duties and obligations, to be induced on the relationship with the communities and the society in general in which the organization is integrated. In some countries, the corporate social responsibility is still a big challenge, since often the actions of social responsibility have not contributed effectively to develop the life situation of much people. This study emphasizes the general perspective of CSR in each one of these countries. CGD - Caixa Geral de Depósitos(Portugal), Vale (Brazil), TechnoLogica (Bulgaria) and IndianOil (India) are important companies concerned with the development of CSR activities; they have some very interesting results in this area.